Adjunct Professor Abdul Halim Ali Visit to the Faculty of Social Sciences, 8 October - 11 October 2012. - Sharifah S., Wan Ahmad (Faculty of Social Sciences, 2012)
For the first visit, there were two main objectives and purposes identified. The special emphasis was on developing and enhancing the capacity of the young academics in the faculty through research and writing workshops. Given Prof Halim’s proven record in guiding the young academics during his tenure as the Chair of Nusantara Studies in the Institute of East Asian Studies (from 2002-2009), it was hoped that similar formula could be replicated during his tenure as the faculty’s adjunct professor. The second objective of his first visit was to assist in the planning and the direction of the ANSOS department, especially on matters relating to research and human capitals. A meeting was held with the head of department and the department-members on 8 October at 11 am to get to know the current state of activities and progress of the department members.